Innovative Uses of Condom Uterine Balloon Tamponade for Postpartum Hemorrhage in India and Tanzania - Jennifer Makin; Daniela I. Suarez-Rebling; Poonam Varma Shivkumar; Vincent Tarimo; Thomas F. Burke (Hindawi Limited, 2018)
Background. Postpartum hemorrhage is the most common cause of maternal deaths worldwide, the majority of which occur in low-resource settings. Uterine balloon tamponade (UBT) is an effective method of addressing uncontrolled postpartum hemorrhage (PPH) from uterine atony; however, UBT devices are often not affordable. We report on three novel uses of an ultra-low-cost condom uterine balloon tamponade (ESM-UBT) device. Cases. ESM-UBT devices were used in innovative ways to arrest severe uncontrolled pregnancy-related hemorrhage among three women in India and Tanzania. The first had sustained deep vaginal lacerations, the second a cervical pregnancy, and the third a complete molar pregnancy. Conclusion. The ESM-UBT device may be useful for control of obstetric hemorrhage caused by complex vaginal tears as well as cervical and molar pregnancies.